Infantile perianal pyramidal protrusion: a case report with dermoscopy and ultrasound findings - Arianna Lamberti (Mattioli1885, 2015)
Infantile perianal pyramidal protrusion, it is a rare benign cutaneous condition described in relatively recent times. It is considered to be under-reported in the pediatric literature because it is often mistaken for other conditions. The unawareness of this lesion may be responsible for an excessive concern both in physician and in parents, which leads to overly aggressive and unnecessary treatments. Thus its recognition has many implications regarding proper management and treatment.